BHS603: Biostatistics / Faculty of Health Sciences - UiTM, / Faculty of Health Sciences (2024)
The aim of the course is to interactively engage students cognitively and scientifically in areas of biostatistics. Students will define concepts, state and explain theories, perform statistical analyses using statistical software via statistical laboratory exercises and in writing, discuss the results and relationships with peers and facilitators. The designated lecture session is used to discuss common biostatistics techniques related to the existing principles or theories in health sciences research. Lecture sessions employ a mixture of lectures and active learning (self and peer discussions). The outcomes shall be accessed through a variety of tools which include the traditional paper examination, informal interviews and classroom engagement.